Iklim Organisasi, Kompetensi, Locus Of Control, Kepuasan Kerja Dan Kinerja ASN - Ni Luh Putu Ary Wahyuni,; Oka Suryadinatha Gorda (Jurnal Ekonomi, 2019)
Performance in carrying out its functions is related to employee job satisfaction and is influenced by skills, abilities and individual traits. The purpose of the study was to determine the effect of organizational climate, competence, locus of control, on job satisfaction and employee performance in the Badan Pendapatan Daerah Kota Denpasar. The sample was determined by 90 people with saturated sampling techniques. The analysis technique uses the structural equation modelling (SEM) model. The results of data analysis show that organizational climate has a significant effect on job satisfaction, competence has a significant effect on job satisfaction, locus of control has a significant effect on job satisfaction, the organizational climate has a significant effect on performance, competence has a significant effect on performance, locus of control has a significant effect on performance. Job satisfaction has a significant effect on the performance of the Badan Pendapatan Daerah Kota Denpasar.